Enteral nutrition tube placement assisted by ultrasonography in patients with severe acute pancreatitis: A novel method for quality improvement. Issue 45 (November 2017) - Li, Gang; Pan, Yiyuan; Zhou, Jing; Tong, Zhihui; Ke, Lu; Li, Weiqin
Abstract : Abstract: To evaluate the effect of a novel procedure using real-time ultrasonography to assist nasojejunal tube placement at bedside in patients with severe acute pancreatitis (SAP). Single center, prospective descriptive study in a 15-bed surgery intensive care unit of a university hospital. Thirty SAP patients were enrolled. The whole procedure of placing nasojejunal tube was performed by a single physician, who places nasojejunal tube at the bedside and performs ultrasonography to guide the tube positioning. The final nasojejunal tube position was confirmed by abdominal radiograph. The successful rate of the procedure as well as the time it took, the time from the decision of enteral feeding to commencement of feeding, and complications were recorded. Thirty-six intubations were performed in 30 patients by using ultrasonography-assisted method at bedside. Nasojejunal tubes were successful placed in 28 of 30 patients (93.3%). The average time of successful placement was 22.07 ± 5.78 minutes. The median time between physician's decision for tube placement and feeding initiation was 5.5 (2, 24) hours. No adverse events occurred in all of patients. This novel method of nasojejunal tube placement under ultrasound guidance is practical, less time consuming and reliable.